MORNING SURGE IN BLOOD PRESSURE AS A PREDICTOR OF WORSENING HEART FAILURE IN HEART FAILURE WITH REDUCED EJECTION FRACTION. (April 2021) - Komori, Takahiro; Hoshide, Satoshi; Kario, Kazuomi
Abstract : Objective: Abnormal circadian blood pressure (BP) rhythm is observed in heart failure (HF) patients. Rising BP in the morning known as the morning surge (MS) is one of the abnormal circadian BP rhythm, and a cardiovascular risk factor in hypertensives. However, the significance of MS is not established in patients with HF. Figure. No caption available. Design and method: We performed a prospective, observational cohort study of hospitalized HF patients who underwent ambulatory BP monitoring (ABPM). Four hundred fifty seven hospitalized HF patients (age, 68 ± 13 yrs; 63.9% males [n = 292] and 36.1% females [n = 165]) were followed up for 20.0 (median) months. Results: HF with reduced ejection fraction (HFrEF) was 197 (43.1%), HF with mid-range ejection fraction (HFmrEF) was 101 (22.1%), and HF with preserved ejection fraction (HFpEF) was 159 (34.8%). The composite outcome consisting of all-cause mortality and worsening HF was observed in 143 patients. In a Kaplan-Meier analysis, the MS group had a significantly higher incidence of the composite outcome than the non-MS group in HFrEF and HFmrEF patients.(figure) However, in multivariate Cox regression analysis, MS was a significant predictor for adverse outcomes only in HFrEF patients (HR 2.63, 95%CI 1.11–6.25, p = 0.03). Conclusions: The MS was found to be a novel predictor of worsening HF in patients with HFrEF.